Cytomegalovirus viral load within blood increases markedly in healthy people over the age of 70 years. Issue 1 (December 2016) - Parry, Helen; Zuo, Jianmin; Frumento, Guido; Mirajkar, Nikhil; Inman, Charlotte; Edwards, Emma; Griffiths, Mike; Pratt, Guy; Moss, Paul
Abstract Background Cytomegalovirus (CMV) is a highly prevalent herpesvirus, which maintains lifelong latency and places a significant burden on host immunity. Infection is associated with increased rates of vascular disease and overall mortality in the elderly and there is an urgent need for improved understanding of the viral-host balance during ageing. CMV is extremely difficult to detect in healthy donors, however, using droplet digital PCR of DNA from peripheral blood monocytes, we obtained an absolute quantification of viral load in 44 healthy donors across a range of ages. Results Viral DNA was detected in 24 % (9/37) of donors below the age of 70 but was found in all individuals above this age. Furthermore, the mean CMV load was only 8.6 copies per 10, 000 monocytes until approximately 70 years of age when it increased by almost 30 fold to 249 copies in older individuals (p  < 0.0001). CMV was found within classical CD14+ monocytes and was not detectable within the CD14-CD16+ subset. The titre of CMV-specific IgG increased inexorably with age indicating that loss of humoral immunity is not a determinant of the increased viral load. In contrast, although cellular immunity to the structural late protein pp65 increased with age, the T cell response to the immediate early protein IE1 decreased in older donors. Conclusion These data reveal that effective control of CMV is impaired during healthy ageing, most probably due to loss of cellular control of early viral reactivation. This information will be of value in guiding efforts to reduce CMV-associated health complications in the elderly.